The influence of magnetic cohesion on the stability of granular slopes - Taylor, Kathryn Helen (2009)
This thesis presents an investigation into the influence of magnetic cohesion on the stability of granular slopes. We consider magnetic cohesion that results from the interaction between dipole moments induced in grains by a uniform magnetic field.